Ciência E Tecnologia Dos Alimentos–Volume 4 2019
DOI: 10.36229/978-85-7042-160-9.cap.04
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade físico-química e microbiológica de marcas comerciais de mel de engenho comercializadas em João Pessoa-PB, Brasil

Abstract: Modo de acesso: World Wide Web Inclui bibliografia 1. Tecnologia de Alimentos 2. Alimentos 3. Nutrição I. Título CDD-664.005 O conteúdo dos artigos e seus dados em sua forma correção e confiabilidade são de responsabilidade exclusiva dos seus respectivos autores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Lopes, D. et al, 2019, the pH and acidity changes of a tucupi were observed after six days of boiling, and it was detected that on the first day of boiling, the pH was 3.7, and on the third day, the value was 3.12. Acidity had its lowest value on the first day with 4.75 meq NaOH.100 mL-1 and its highest on the fifth day with 9.06 meq NaOH.100 mL-1.…”
Section: Physical-chemical Characterizationmentioning
confidence: 99%
“…In Lopes, D. et al, 2019, the pH and acidity changes of a tucupi were observed after six days of boiling, and it was detected that on the first day of boiling, the pH was 3.7, and on the third day, the value was 3.12. Acidity had its lowest value on the first day with 4.75 meq NaOH.100 mL-1 and its highest on the fifth day with 9.06 meq NaOH.100 mL-1.…”
Section: Physical-chemical Characterizationmentioning
confidence: 99%